Efeitos de oito semanas de atividades psicomotoras no desenvolvimento motor de escolares do 1º ano do ensino fundamental I - MARINHO, Paloma Lays Fonseca (2024)
Aim: To check the effects of eight weeks of psychomotor activities on the motor development of elementary school children. Materials and Methods: 27 schoolchildren of both sexes took part, chosen for convenience at the Waldir Filho Integrated Unit, a municipal school. The Motor Development Scale (MDS) was used for the psychomotor assessment. After the initial assessment, 16 50-minute sessions of psychomotor activities were carried out twice a week, with the Motor Development Scale being reapplied at four weeks and then at eight weeks. Fine and global motor skills, balance, body schema, spatial and temporal organization and laterality were measured. The data was treated statically, descriptively and analytically Results: The results showed that after the intervention there was a better improvement in fine motor skills, global motor skills and balance, while temporal and spatial organization, although there was an improvement in the motor scale, was still below what was expected for the students' chronological age. Conclusion: The intervention offered to the schoolchildren improved motor development, especially global motor skills and balance, thus indicating that psychomotor activities are essential for this purpose.